Annual Plan 2001-02 State Planning Board Thiruvananthapuram - Planning Commission (Planning Commission, 2000)
During the Annual Plan period 2001-02, main emphasis will be on completion of all major projects taken up during Ninth Plan such as power, irrigation and water supply. Thrust will be given for the timely execution of projects aimed at infrastructure development as well as those involving financial support from external funding agencies and financial institutions. Programmed for the accelerated growth of agriculture and industries have been provided with sufficient outlays. The schemes for providing houses to the people belonging to weaker sections by constructing five lakh houses in three years from 1999-2000 and complete coverage of houses for the houseless among SCs/STs will be implemented vigorously in 2001-02. An amount of Rs. 1065 crores has been set apart as grant in aid to local bodies as State support for implementing their need based development schemes with people’s involvement.
State Planning Board Thiruvananthapuram